Fast carbon dioxide-epoxide cycloaddition catalyzed by metal and metal-free ionic liquids for designing non-isocyanate polyurethanes - Rebei, Marwa; Červinka, Ctirad; Mahun, Andrii; Ecorchard, Petra; Honzíček, Jan; Livi, Sebastien; Donato, Ricardo K; Beneš, Hynek (ROYAL SOC CHEMISTRY, 2024)
The recycling of industrially produced greenhouse gases, such as CO2, into high-value-added chemicals is one of the most relevant strategies for reaching climate targets. Herein, we present a two-step strategy for how to efficiently convert renewable carbon dioxide (CO2) into beta-hydroxyurethanes using imidazolium ionic liquids (ILs) bearing metal ([ZnCl4]2- and [CoCl4]2-) or Cl- IL-anions as all-in-one catalysts. The first step involves the rapid (1 h) conversion of phenyl glycidyl ether using ILs and supercritical carbon dioxide (7.7 MPa, 80 degrees C) to cyclic carbonates in high yield (98%). The DFT calculations suggested a comprehensive mechanistic pathway for the IL-catalyzed CO2-epoxy reaction showing a rate-determining step of the initial epoxide ring opening and the direct participation of IL-anions. Moreover, the applied ILs are also able to catalyze the subsequent reaction of the formed cyclic carbonates with butylamine resulting in fast formation of beta-hydroxyurethanes. Thus, the present concept seems to be a promising strategy for designing non-isocyanate polyurethanes (NIPUs). Imidazolium-based ionic liquids are applied as all-in-one catalysts for the supercritical carbon dioxide-epoxide cycloaddition to produce beta-hydroxyurethanes under mild conditions.
Rychlá cykloadice oxidu uhličitého a epoxidu katalyzovaná iontovými kapalinami bez kovů a kovů pro design neisokyanátových polyuretanů
Keywords: ring-opening polymerization; cyclic carbonates; efficient catalysts; organic framework; co2 fixation; capture; density; copolymerization; polycarbonates; temperature